Zusammenhang zwischen der Mehrzweckselektierung und der Zuverlässigkeit im Bauwesen - Zavadskas, Edmundas K. (Journal of Civil Engineering and Management, 1996)
The relationship between the criteria of multipurpose selection and the characteristics of reliabilityThe rationality of functioning of either the technical or the organizing-technological system is characterized by the criteria of multipurpose selection that express the usefulness of the variants under consideration. When evaluating the usefulness of a variant, it is necessary to take into consideration its reliability. Therefore, the given method investigates into the relationship between the criteria of multipurpose selection and the characteristics of reliability.Daugiatikslės selektonovacijos ir patikimumo ryšys statybojeSantrauka. Techninės ir organizacinės technologinės sistemos funkcionavimo racionalumas gali būti apibūdinamas daugiatikslės selektonovacijos kriterijais, kurie išreiškia nagrinějamų variantų naudingumą. Įvertinant varianto naudingumą svarbu alsižvelgti ir į jo patikimumą. Todėl straipsnyje pateikta metodika, nagrinėjanti daugiatikslės selektonovacijos kriterijų ir patikimumo charakteristikų priklausomybę.Article in German.First Published Online: 26 Jul 2012